Using Social Media to Gauge Iranian Public Opinion and Mood After the 2009 Election - Elson, Sara Beth (RAND Corporation, 2012)
In the months after the contested Iranian presidential election in June 2009, Iranians spoke out about the election using Twitter--a social media service that allows users to send short text messages, called tweets, with relative anonymity. This research analyzed more than 2.5 million tweets discussing the Iran election that were sent in the nine months following it, drawing insights into Iranian public and mood in the post-election period.